(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: All human faces are unique and contribute to individual identity. The face is oneof the most fundamental parts of the body for self-recognition. Objectives: To measure the facialgolden ratio (FGR) and facial appearance (FA) of medical students of Jouf University, SaudiArabia. Methodology: This is a cross sectional study, facial height (FH) and facial width (FW)of each participant were measured by digital verniercalliper. All measurements were done bytwo researchers, if the measurements are equal or nearby, then mean value are considered andassessment of facial awareness are done by a validated structured questionnaire. Data analysiswas carried out using the Statistical Package for Social Sciences version 23 (SPSS Inc., Chicago,IL, USA). Results: Mean FGR value of the males and females are 1.64 and 1.55 respectively.This study revealed highly significant disparities among genders. The male participant has closeresembles with FGR in comparison to females. There was no significant difference betweenupper FH (57.74), Middle FH (55.16) and Lower FH (56.65) among Saudi, Jordan and Syrianparticipant. The females were significantly more satisfied with their eyelids and eyes than males,and their significant different was p=0.014 and 0.002, respectively. Conclusions: Majoritypopulation, both male and female having a normal face and satisfied with their face’s variables.The male participant has close resembles with the FGR. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.334-341